Ethnopharmacological insights into uterine fibroids: a review of etiology, and therapeutic potential of natural products - Manzane, Gcobisa Valencia; Modise, Joe Sekomeng; Okoli, Bamide Joseph; Mtunzi, Fanyana; Monapathi, Mzimkhulu Ephraim (Frontiers in Pharmacology, 2026)
Uterine fibroids (leiomyomas) are the most common benign gynecologic tumors, affecting up to 80% of women by age 50, with higher prevalence and symptom severity reported in women of African descent. These monoclonal tumors originate from smooth muscle cells of the myometrium and are classified based on anatomical location (intramural, submucosal, subserosal, or transmural). Clinical manifestations include abnormal uterine bleeding, pelvic pain or pressure, and infertility. The pathogenesis of fibroids is multifactorial, involving hormonal dysregulation (particularly estrogen and progesterone), MED12 gene mutations, extracellular matrix accumulation, and modifiable risk factors such as vitamin D deficiency and obesity. This review synthesizes current knowledge on fibroid etiology, and treatment strategies, with specific focus on the ethnopharmacological relevance of botanical drugs and natural products. Conventional therapies, including surgery and hormone-based medications, are effective but often associated with high cost, side effects, or loss of fertility. In contrast, natural therapies such as vitamins (D, E), epigallocatechin gallate (EGCG), and plant-based formulations offer promising but underexplored alternatives. Special emphasis is placed on Gunnera perpensa L. [Gunneraceae; Gunnerae perpensae radix] and Albizia tanganyicensis Baker [Fabaceae; Albiziae cortex], two species used in South African traditional medicine for gynecological disorders. Ethnobotanical use, phytochemical profiles, and pharmacological activities including anti-inflammatory, antioxidant, anti-proliferative, and uterotonic properties are critically reviewed. Botanical names have been validated, and data were assessed using the Four Pillars of Best Practice in Ethnopharmacology, the ConPhyMP framework, and the GA checklist for reproducibility and quality assurance. By bridging traditional knowledge with current scientific evidence, this review supports the potential role of culturally rooted botanical drugs in integrative fibroid management and highlights directions for future pharmacological and clinical research.